Patanjali Yoga Practice and its Effect on Mental Health and Moral Judgment Amongst Juvenile Delinquents (Indian Journal of Public Health Research & Development, 2020)
Research awareness and involvement in yoga for health-related results are growing worldwide. PatanjaliYoga relieves stress and fatigue which haves turned into one of the few major challenges confrontingthe medical fraternity in present times. Yoga let go the body from any type of muscular or chronic strainand rejuvenates the body from exhaustion, body aches, stress, aids to ease the body and mind, enhancesconcentration and alertness, and frees the soul. It helps one to create integrity amongst his outward selfas well as his innermost self. If the practices are followed meticulously then Patanjali Yoga develops aconstructive effect both in the inward and outer selves of an organism. Patanjali’s yoga practice aims tobind the individual self with the Ultimate One and one can achieve this union by regulating and discardingthe ever- arising ‘vrittis’ or amendments of the mind. With Patanjali Yoga mind can be balanced throughthe exact kind of discipline and training. The purpose of this paper was to study the effect of Patanjali Yogapractice on mental health and moral judgment of experimental group of juvenile delinquents. Pre and postexperimental design was used in this research work. Patanjali Yoga practices were used as independentvariables whereas mental health and moral judgments of delinquents as dependent variables. A sample of 70delinquents of age group (13-18 years) from Government Observation Home in Agra district was chosen withrandom selection method. There were two groups –experimental group (n=35) and control group (n=35).Patanjali Yoga practices were imparted to delinquents for 90 days with duration of one hour each day. Formeasuring the moral judgment of delinquents, moral judgment test by Juri Baruh (2004) and for measuringmental health, mental health battery by A.K. Singh and Alpana SenGupta (2008) were used. Mean, Standarddeviation and t-test were carried out for data analysis. The findings suggest that mental health factors likeemotional stability, adjustment, autonomy, security-insecurity and self-concept were found to be of averagelevel and intelligence ranged from average to low in experimental and control group delinquents. It was alsofound that Patanjali Yoga plays a significant role by strengthening emotional stability, adjustment and self-concept in delinquents, however, the Patanjali yoga does not significantly affects mental health factors likeautonomy, security-insecurity and intelligence in delinquents. The findings also concluded that PatanjaliYoga does not affect moral judgments of delinquents.
Keywords: Patanjali Yoga, Mental Health, Moral Judgment, Juvenile Delinquents.